2020
DOI: 10.1111/pbr.12855
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analysis of resistance to Pythium ultimum in common bean (Phaseolus vulgaris)

Abstract: Common bean is the most important edible grain legume and dietary component in the world (Gepts et al., 2008). Bean contributes significantly to food and nutritional security of millions in sub-Saharan Africa and the developing world, providing a cheap protein source and micronutrients such as iron and zinc (Broughton et al., 2003; Graham et al., 2007), and income for smallholder farmers. However, productivity of common bean in many parts of Central and South America, and Africa is constrained by several disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…The traits Pyth_COL (P. myriotylum response in the greenhouse) RRD_field (root rot damage in the field) and RRD_all (root rot damage combining both datasets) were evaluated in the RR panel in Colombia (COL). The traits Fus_UGA (F. cuneirostrum), Pyth_UGA (P. ultimum), Rhiz_USA (R. solani) and Fus_USA (F. solani) were evaluated in the ADP panel in Uganda (UGA) (Amongi et al, 2020;Onziga Dramadri et al, 2020) and the USA (Oladzad et al, 2019;Zitnick-Anderson et al, 2020). The ALS response was evaluated in the extBALSIT panel in Colombia (COL) and Uganda (UGA) (Nay et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The traits Pyth_COL (P. myriotylum response in the greenhouse) RRD_field (root rot damage in the field) and RRD_all (root rot damage combining both datasets) were evaluated in the RR panel in Colombia (COL). The traits Fus_UGA (F. cuneirostrum), Pyth_UGA (P. ultimum), Rhiz_USA (R. solani) and Fus_USA (F. solani) were evaluated in the ADP panel in Uganda (UGA) (Amongi et al, 2020;Onziga Dramadri et al, 2020) and the USA (Oladzad et al, 2019;Zitnick-Anderson et al, 2020). The ALS response was evaluated in the extBALSIT panel in Colombia (COL) and Uganda (UGA) (Nay et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We observed a similar trend in the RR and extBALSIT populations, but it was not the case for the ADP evaluations in Uganda (Figure 5), where the PA fell by around 40 points below the estimated heritability. This result can be attributable to the binary distribution with presence/absence scores that the original data display (Amongi et al, 2020;Onziga Dramadri et al, 2020), which confers high heritability estimates, and the RKHS model evaluated in this study, which performed the prediction of a trait with quantitative nature. Wen et al (2019) confirmed that traits with high heritability would have higher PAs.…”
Section: Genomic Prediction For Root Rot Diseasementioning
confidence: 98%
See 2 more Smart Citations
“…The availability of high‐density, genome‐wide SNP markers has made genome‐wide association study (GWAS) a useful approach for identifying marker loci associated with causative variation in important traits in a diverse germplasm collection. In common bean, GWAS has been used for mapping genomic regions associated with a number of traits of economic importance, including phenology and yield component traits, cooking time, and disease resistance (Cichy et al., 2015; Dramadri et al., 2020; Hoyos‐Villegas et al., 2017; Kamfwa et al., 2015; Zuiderveen et al., 2016). The development of bean cultivars with enhanced tolerance to DS can be improved through the identification of genomic regions and associated key agronomic and PS traits and a better understanding of the genetic control and physiological mechanisms associated with the key traits regulating drought tolerance.…”
Section: Introductionmentioning
confidence: 99%